Intraoperative Partial Pressure of Oxygen Measurement to Predict Flap Survival - Tahir, Muhammad Raza; Khalid, Kamran (Biological and Clinical Sciences Research Journal, 2025)
Flap survival is a critical factor in reconstructive surgery, with ischemia-related complications leading to necrosis and surgical failure. Current methods for intraoperative flap assessment are often subjective, creating a need for an objective, real-time measure of tissue viability. The partial pressure of oxygen (pO₂) may serve as a reliable predictor of flap survival, allowing for early intervention and improved surgical outcomes. Objective: Our study set out to explore whether the intraoperative measurement of the partial pressure of oxygen (pO₂) could reliably predict flap survival in reconstructive surgery, aiming to pinpoint a practical tool for surgeons to assess tissue viability during operations. Methods: We enrolled 70 patients, all aged 18 years and above, who were undergoing flap procedures at our institution. Flap types varied across pedicled, free, fasciocutaneous, and musculocutaneous designs. Intraoperatively, we maintained a consistent fraction of inspired oxygen at 50% and, at 30 minutes post-flap inset, collected capillary blood samples from proximal, middle, and distal flap regions, alongside a fingertip control, using heparinised syringes. These samples were analysed with a blood gas machine to determine pO₂ and diff-pO₂ values, while flap survival was later judged clinically by tissue health, with complications like thrombosis or hematoma noted during surgery. Results: The mean flap pO₂ stood at 105.34 mmHg (±21.479), finger pO₂ at 149.20±16.909 mmHg, and diff-pO₂ at 75.81±26.417 mmHg. Survival reached 82.9%, while complications were sparse, showing thrombosis in 7.1% and hematoma in 4.3%. Pedicled flaps, making up 57.1% of cases, appeared most prone to necrosis. Conclusion: We conclude that this approach could guide timely interventions, though further refinement of pO₂ cutoffs and risk factors is needed to sharpen its clinical impact.